A qualitative analysis of the curing depth of visible light cured composite resin as determined by a color dye - Fernandez, Stella Maris D.
Class III cavity preparations were done on maxillary central incisors to receive visible light-cured composite fillings on either the mesial or distal surface. The teeth were then sectioned mesiodistally, passing the center of the restoration, and then immersed in a solution of copper phthalocyanine Astra Blue dye. The specimen were then examined under a stereo-microscope to locate areas of incomplete polymerization, as indicated by the blue-stained regions. It was found that visible light-cured composite fillings were completely polymerized to a depth of 3 mm., and that prolonging the exposure time from 20 seconds to 40 seconds did not show significant improvement in the degree of curing of the visible light-cured composite resin.